Impacts of sulfur oxides on mercury speciation and capture by fly ash during oxy-fuel pulverized coal combustion - Belo, Lawrence P. (Animo Repository, 2016)
Coal-fired utility boilers are the single largest anthropogenic source of mercury emissions. Mercury is a naturally occurring trace element in coal and, when combusted, may exist in three different forms: Hg0, Hg2+, or Hg particulate. During oxy-fuel combustion, impurity concentrations, such as SOx, NOx, and Hg, can be up to 4 times higher than concentrations in air combustion. An increased mercury concentration is of concern because mercury is known to attack aluminum heat exchangers required in the compression of CO2. As a result of the elevated concentrations during oxy-fuel conditions, interactions of Hg and SOx were investigated in this study to verify if there is any competition between SOx and Hg. The effect of Hg, SOx, H2O, and temperature on the native capture of Hg by fly ash was assessed using a quartz flow reactor packed with fly ash to simulate a bag filter. Doubling Hg in the system from 5 to 10 μg/Nm3 doubled the amount of Hg captured in the fly ash from 1.6 to 2.8% and increased the amount of Hg unaccounted from 5.8 to 18.1%. Increased SO2 decreased the proportion of Hg0 in the flue gas. The temperature in the bag filter was found to have a large impact on the mercury capture by fly ash. As the temperature was increased from 90 to 200 °C, Hg0 in the flue gas was found to increase from 77.9 to 98.3%, indicating better capture of Hg at lower temperatures. © 2016 American Chemical Society.